2016
DOI: 10.1590/18069657rbcs20150444
|View full text |Cite
|
Sign up to set email alerts
|

Litter Decomposition of Two Pioneer Tree Species and Associated Soil Fauna in Areas Reclaimed after Surface Coal Mining in Southern Brazil

Abstract: Decomposition of leaf litter from pioneer tree species and development of associated soil meso-and macrofauna are fundamental for rehabilitation processes in reclaimed coal mining areas. The aim of our study was to evaluate decomposition of Schinus terebinthifolius and Senna multijuga to answer three basic questions: (i) What type of leaf litter degrades faster in reclaimed coal min\ing areas? (ii) Is leaf decomposition correlated with the stage of regeneration and exposure time? and (iii) Does the type of lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
2
1
1
4
Order By: Relevance
“…in the natural soil under native vegetation and in the mined soil under revegetation. This result differs from those of Frasson et al (2016) andOliveira Filho et al (2014) who observed a predominance of springtails over mites in coal mining areas under revegetation for 5 and 7 years, respectively, with different plant species (Schinus.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…in the natural soil under native vegetation and in the mined soil under revegetation. This result differs from those of Frasson et al (2016) andOliveira Filho et al (2014) who observed a predominance of springtails over mites in coal mining areas under revegetation for 5 and 7 years, respectively, with different plant species (Schinus.…”
Section: Resultscontrasting
confidence: 99%
“…In this sense, several studies have already been developed in mining soils to evaluate the effect of revegetation on their chemical (Bitencourt et al, 2015;Stumpf et al, 2016a;Leal et al, 2016), physical (Reis et al, 2014;Stumpf et al, 2016b;Pauletto et al, 2016) and biological (Menta et al, 2014;Oliveira Filho et al, 2015;Frasson et al, 2016;Majumder & Palit, 2017) attributes. Plants play a key role in the recovery of degraded areas, since they promote the increase of organic matter and the improvement of other soil attributes such as aggregation, aeration and water retention, thus creating favorable conditions for increasing the diversity of edaphic organisms, which in turn, influence nutrient recycling and consequently improve soil fertility and ecological balance (Hernani & Padovan, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Portanto, a remoção da serapilheira influencia negativamente a comunidade de artrópodes do solo de maneira direta e indireta, em ecossistemas florestais (SAYER, 2006). O desfavorecimento de diferentes guildas tróficas indica que o ambiente edáfico é menos estável (FERREIRA et al, 2017), sendo que esta condição, que prejudica a dinâmica da decomposição de serapilheira e, dessa forma, a ciclagem de nutrientes (FRASSON et al, 2016), está associada à remoção da camada de serapilheira.…”
Section: Resultsunclassified
“…Em laboratório, com o auxílio de pinças e lupas de mão, foi realizada a extração e triagem dos exemplares de invertebrados da macrofauna edáfica, nos monólitos provenientes das amostras de solo e serapilheira, com esforço amostral de aproximadamente 30 minutos por amostra. Os invertebrados extraídos foram acondicionados em frascos contendo álcool 70%, para conservação e posterior identificação, que se deu em grandes táxons ao nível de ordem taxonômica (Dos SANTOS et al, 2015).…”
Section: Coleta Amostragem Identificação E Análiseunclassified